Structural and mechanistic basis of differentiated inhibitors of the acute pancreatitis target kynurenine-3-monooxygenase - Jonathan P. Hutchinson (Nature Portfolio, 2017)
Kynurenine-3-monooxygenase (KMO) is an emerging clinical target for treatment of neurodegenerative diseases and acute pancreatitis. Here, the authors report potent inhibitors that bind KMO in an unexpected conformation, offering structural and mechanistic insights for future drug discovery ventures.